2014
DOI: 10.1080/02602938.2014.931926
|View full text |Cite
|
Sign up to set email alerts
|

Student attitudes to blogs: a case study of reflective and collaborative learning

Abstract: The aim of this study is to evaluate the capacity of an e-learning tool (blog) to facilitate reflection among students as part of collaborative group learning. The paper provides insights into student attitudes towards blogs as an interactive and reflective learning tool. Additionally, the study highlights the differences between domestic and international student attitudes towards reflection as part of collaborative learning in groups. The results indicate that international students consistently viewed the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
(31 reference statements)
0
10
0
2
Order By: Relevance
“…For example, wikis have been employed by educators to facilitate peer scaffolding and feedback in collaborative writing tasks (Athanassios & Dimitrios, 2017;Moskaliuk, Kimmerle, & Cress, 2012). Blogs have also been used to engage students in reflective learning and knowledge sharing (Chawinga, 2017;Jackling, Natoli, Siddique, & Sciulli, 2015;Laru, Näykki, & Järvelä, 2012). In addition, dialogic interaction between students, and also with teachers, can be stimulated through the use of online discussion forums (Kear, Woodthorpe, Robertson, & Hutchison, 2010;P.-Y.…”
Section: Review Of Current Researchmentioning
confidence: 99%
“…For example, wikis have been employed by educators to facilitate peer scaffolding and feedback in collaborative writing tasks (Athanassios & Dimitrios, 2017;Moskaliuk, Kimmerle, & Cress, 2012). Blogs have also been used to engage students in reflective learning and knowledge sharing (Chawinga, 2017;Jackling, Natoli, Siddique, & Sciulli, 2015;Laru, Näykki, & Järvelä, 2012). In addition, dialogic interaction between students, and also with teachers, can be stimulated through the use of online discussion forums (Kear, Woodthorpe, Robertson, & Hutchison, 2010;P.-Y.…”
Section: Review Of Current Researchmentioning
confidence: 99%
“…Our findings echo several previous studies (for example. Jackling et al, 2015;Ette & Stoker, 2015;Park et al 2011) that students can have a better understanding of their learning through blogging if they are encouraged to formally reflect on that learning. Another finding was that the student-teachers in our study were empowered by the positive feedback they received.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, McLoughlin and Lee (2010) found that students did not provide feedback to their allocated partner, and instead responded to only those other students whom they shared common interests with as they were to their allocated partners' postings. Jackling, Natoli, Siddique & Sciulli (2015) evaluated the capacity of blogs to facilitate reflection among students as part of collaborative group learning in an Australian higher education institution. Student perceptions towards blogs indicate that although blogs were an interactive and reflective learning tool, they were disappointed working in groups.…”
Section: Perceptions Of Multi-author Blogs As Tools To Support Collabmentioning
confidence: 99%
“…En este sentido, "se espera que los estudiantes en Educación Superior participen activamente en el pensamiento crítico y la creación de conocimiento, en lugar de la recepción pasiva de un conocimiento dado" (Lee et al, 2015: p.31). El objetivo de las actividades de prácticas reflexivas es el fomento del aprendizaje profundo y la preparación de los estudiantes para las demandas profesionales, mediante el aprendizaje colaborativo en grupos (Jackling et al, 2015). En definitiva "el objetivo final de cualquier programa que pretenda desarrollar la reflexión no ha de ser otro que el de fomentar en los futuros profesionales habilidades metacognitivas que les permitan interrogar, analizar, conocer, evaluar y modificar su propia práctica desde un punto de vista profesional, moral y social" (Moya et al, 2010: p.13).…”
Section: Marco Conceptual 21 El Uso De La Investigación Cualitativa unclassified